Remote measurement of fire parameters of the industrial accelerator electron gun - Mats, V.O.; Romanovsky, S.K.; Titarenko, Yu.O.; Titov, V.Yu.; Tur, Yu.D. (Вопросы атомной науки и техники, 2021)
A device designed for continuous remote control of the parameters of the incandescent circuit of the electronic gun of the accelerator LU-10 has been developed. The created device allows to measure with galvanic isolation of electric quantities of operating voltage and current which are under potential of 5 kV concerning the earth bus. Розроблено пристрій, призначений для безперервного дистанційного контролю параметрів розжарювального ланцюга електронної гармати прискорювача ЛП-10. Створений пристрій дає можливість вимірювання з гальванічною розв'язкою електричних величин, що знаходяться під потенціалом 5 кВ щодо земляної шини. Разработано устройство, предназначенное для непрерывного дистанционного контроля параметров накальной цепи электронной пушки ускорителя ЛУ-10. Созданное устройство дает возможность измерения с гальванической развязкой электрических величин, находящихся под потенциалом 5 кВ относительно земляной шины.